Implementasi Kurikulum Tingkat Satuan Pendidikan (KTSP) dalam Sistem Pendidikan Indonesia: Studi Literatur - Aksya Robbi Iqrom; Bagas Andre Yansyah; Mohamad Muspawi (STKIP Subang, 2026)
This study aims to analyze the implementation of the School-Based Curriculum (KTSP) in the Indonesian education system, including its implementation concept, classroom application, supporting and inhibiting factors, and its relevance to curriculum development in Indonesia. The study employed a qualitative descriptive literature review method. Data were collected from 20 relevant sources, consisting of scientific journal articles and books published between 2007 and 2025. The findings show that KTSP provides schools and teachers with greater flexibility to develop curricula and learning activities based on students’ characteristics, school conditions, and local potential. Its implementation encourages learning that is more flexible, contextual, and student-centered. However, several challenges remain, such as limited teacher understanding, insufficient training, differences in school readiness, and inadequate facilities and infrastructure. Although Indonesian education has evolved into the 2013 Curriculum and the Merdeka Curriculum, the fundamental principles of KTSP, such as school autonomy and learning flexibility, remain relevant to current curriculum development in Indonesia.